Identification guide to genera of aquatic larval Chironomidae (Diptera) of Australia and New Zealand - Cranston, Peter S. (Zootaxa, 2019)
Identification keys are provided for the final (4th) instar larvae of genera of Chironomidae (Diptera), from aquatic habitats in Australia and New Zealand. Morphological features of taxonomic utility are discussed and illustrated by line drawings. Summaries of described species for each genus and their distribution is provided, with reference to means of further identification where available. In the subfamily Podonominae, 5 genera are keyed of which 3 are recorded from New Zealand; the 4 genera of Aphroteniinae are from Australia (absent from New Zealand); in Diamesinae 1 genus is Australian, 2 are from New Zealand; in the Tanypodinae 21 genera are found in Australia and 4 are from New Zealand; in Orthocladiinae 31 genera are reported from Australia, 14 from New Zealand; and in Chironominae 43 genera are keyed from Australia, 9 from New Zealand. Larvae of Axarus Roback, Chernovskiia Sæther and Omisus Townes (Chironomini) are recognised in Australia for the first time. The undescribed larva of Paucispinigera Freeman, endemic to New Zealand, is keyed and several other New Zealand taxa are included based on unpublished records. Genera reported from Australia and New Zealand as adults, but unknown as larvae, are listed.